Drought-induced cyanogenesis in sorghum (Sorghum bicolor L.): Genotypic variation in dhurrin biosynthesis and stress response - Katamreddy, S.C.; Jose, J.; Reddy, B.P.; Sivasakthi, K.; Sanivarapu, H.; Dube, N.; Gaddameedi, A.; Prasad, Kodukula V.S.V.; Yogendra, K.; Govindaraj, M.; Kholova, J.; Choudhury, S.R.; et al. (Wiley, 2026)
The accumulation of the livestock-harming cyanogenic glucoside dhurrin in the vegetative tissues limits the use of sorghum as a major pasture crop. This study integrates transcriptomics and metabolomics data from the ICSV 93046, CSH 24-MF and ICSR 14001 genotypes, which differ in drought tolerance and cyanide potential (HCNp), to understand the molecular processes of cyanogenesis under drought stress conditions. While ICSV 93046 showed drought adaptation and reduced HCNp, ICSR 14001 and CSH 24-MF exhibited decreased drought stress tolerance with HCN accumulation. The differentially expressed gene (DEG) data showed drought-related genes were significantly upregulated in ICSV 93046 but downregulated in ICSR 14001. KEGG pathway analysis revealed enriched dhurrin biosynthesis and cyanoamino acid metabolism genes, with higher expression in ICSR 14001 than in ICSV 93046. WGCNA analysis revealed that hub genes are involved in drought-induced signalling components, such as phospholipases (PLPs) and lipoxygenases (LOXs), which are implicated in membrane protection. In drought-sensitive genotypes, stress-induced membrane damages lead to the release of dhurrin into the cytoplasm, thus elevating HCN content and activating defence responses. Conversely, the drought-adapted genotype could mitigate HCN production by averting membrane injury, thereby effectively modulating the oxidative stress and preventing the release of dhurrin into the cytoplasm.